Design and assessment of AI-enabled sustainable HR practices affecting employee performance with engagement mediation and personality moderation in the Indian IT industry - Thangaraju, Karthikeyan; Palani, Poonguzhali (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the impact of AI-enabled sustainable HR practices on employee performance in India's IT industry. The problem addressed is the lack of empirical evidence on how AI-driven HR practices influence performance, with a focus on the mediating role of employee engagement and the moderating role of conscientiousness. The research responds to the vital question of how AI-based HR innovations, which include AI-based recruitment and development, AI-enabled performance feedback, organizational sustainability orientation, and AI-based employee empowerment, influence the performance of IT professionals. Data were collected from 340 Indian IT professionals using structured instruments with snowball sampling method. The findings explore the impact of AI-based HR practices on employee performance in the Indian IT industry. The findings show significant positive effects of AI-driven recruitment (β = 0.116, p = 0.007), performance management (β = 0.180, p < 0.001), and training (β = 0.204, p < 0.001). Employee engagement mediates these relationships (β = 0.136, p = 0.002), while conscientiousness moderates the engagement-performance link (β = 0.150, p = 0.006). From a practical point of view, the results suggest that it is important for IT managers to adopt future-oriented and viable HR digital solutions that capitalize on both technology and human elements in an effort to enhance productivity in an industry in which the pace of change is rapid